Mathematics In Context: A Lesson For Teaching Geometric Sequences In High School - Niska Bonitasia Zendrato; Syafi’i; Ellis Mardiana Panggabean; Tua Halomoan Harahap (Yayasan pendidikan dzurriyatul Quran, 2025)
Learning design is an important framework in the educational process designed to achieve learning objectives effectively and efficiently. This research aims to analyze the teaching of Geometric Rows material in Class X SMA (Senior High School) using the Problem base Learning approach. This research uses design research method. The results of this study reveal that design research with a preliminary design stage succeeded in developing an “Iceberg” and HLT-based learning trajectory on geometric row material that was effective in facilitating students' concept understanding gradually. This learning trajectory is designed through stages ranging from real contexts to abstract models, so that students can understand the patterns and formulas of geometric rows in depth. At the contextual level, the introduction of real problems helps students relate mathematical concepts to everyday life, increasing learning motivation. At the concrete model level, students are able to visualize the geometric sequence pattern through manipulation of objects and tools, so that they understand the relationship between terms intuitively. Furthermore, at the abstract model level, students are not only able to use the geometric sequence formula correctly, but also understand the conceptual basis behind it. Finally, at the generalization level, students are able to solve various application problems, showing critical thinking skills and a deeper understanding of the concepts.